Biogas Production from Solid Jamu Waste Production Traditional with Anaerobic Process Liquid State – Anaerobic Digestion (LS - AD) Method - Siswo Sumardiono; Bakti Jos; Abdullah Farhan; Nearya Sondang; Heri Cahyono (Waste Technology, 2022)
Biogas is a flammable gas produced from the fermentation process of organic materials by anaerobic bacteria. The principle of making biogas is the anaerobic decomposition of organic matter (closed from free air) to produce gas, mostly methane (CH4) and carbon dioxide (CO2). One source of organic material that can be used as raw material for making biogas is the waste contents of the beef rumen. The anaerobic decomposition process is assisted by a number of microorganisms, especially methane-producing bacteria. The first generation of biogas is biogas produced by food derivatives and the process is still conventional. One of the agricultural wastes that can be developed into biogas is jamu waste. Jamu dregs contain high crude fiber, which is 39.72% of the dry weight. Where crude fiber is thought to help in the fermentation process. This research will examine the effect of time on biogas production with the composition of the raw material for jamu waste, the effect of pre-treatment of C/N ratio on biogas production and the effect of Total Solid Substrate on biogas production. Biogas production is carried out through hydrolysis, acidogenesis and methanogenesis stages. The total solid ratio are set in Liquid State condition with 3, 7, 11 and 15% variant of total solid content and the pretreatment of the nutrient ratio of the substrate C/N 20, 22, 24 and 26. The biogas formation process was carried out for 2 months, with a quantitative test response in the form of biogas volume and CODMn removal per 2 days.